Genetical, Cytological & Biological Studies of Chrysomya bezziana Vill. (Diptera: Calliphoridae) Exposed to Gamma Rays: I. Effect on Adult Emergence & Sex Ratio - L. J. M. AL-Bahadlyli; A. A. R. AL-Taweel; B. M. A. AL-Azawi (مجلة بغداد للعلوم)
the results of this study showed that irradiated pupae at age of one day old was very sensitive to all doses of gamma rays.